2010
DOI: 10.1002/nml.20006
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit mission statement focus and financial performance

Abstract: Mission statements have been adopted nearly universally in nonprofit organizations. Their ubiquity is based on a presumption that a well-designed missionC URRENT WISDOM IN THE NONPROFIT SECTOR holds that a mission statement is a critical tool for achieving organizational success, but the academic literature has not convincingly demonstrated evidence to confirm this widely held assumption. The purpose of this exploratory article is to determine whether or not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 47 publications
1
83
1
1
Order By: Relevance
“…Despite the importance of mission statements as a strategic management tool, this critical organizational communiqué in the nonprofit context has been examined in only a limited number of studies (for example, Brown, Yoshioka, and Munoz ; Kirk and Nolan ). Extant literature from other sectors has concluded that mission statements are tools for exercising leadership (Klemm, Sanderson, and Luffman ), clarifying organizational goals (Bart ; Pearce and David ), establishing effective public relations (Bart ; David ), and generating interest in the organizational purpose (Bartkus, Glassman, and McAfee ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of mission statements as a strategic management tool, this critical organizational communiqué in the nonprofit context has been examined in only a limited number of studies (for example, Brown, Yoshioka, and Munoz ; Kirk and Nolan ). Extant literature from other sectors has concluded that mission statements are tools for exercising leadership (Klemm, Sanderson, and Luffman ), clarifying organizational goals (Bart ; Pearce and David ), establishing effective public relations (Bart ; David ), and generating interest in the organizational purpose (Bartkus, Glassman, and McAfee ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, attitudes toward mission statements vary. Whereas some consider mission statements to be perfunctory, others believe that these “statements of purpose” are central drivers of organizational strategies (Bart ; Kirk and Nolan ; Swales and Rogers ). Mission statements also represent the organization in its artifacts, for example, newsletters, annual reports, brochures, posters, and business cards (Fairhurst, Jordan, and Neuwirth ), and can influence stakeholder perceptions of the organization and its activities.…”
mentioning
confidence: 99%
“…The classification allows the stakeholders to assess the priorities among the cooperatives. Prior studies suggested that mission statement contents of nonprofit organizations do not relate consistently to performance (Kirk & Nolan, 2010). This in fact is contrary to profit-oriented organizations whereby the mission statement contents relates positively to company's performance (Bartkus & Glassman, 2008;Blair-Loy, Wharton, & Goodstein, 2011).…”
Section: Content Priorities Of Cooperatives Mission Statementsmentioning
confidence: 90%
“…At a time of major financial constraints, nonprofit sports clubs are faced with new and complex challenges, in particular regarding their own organizational efficiency levels. In striving to achieve their objectives, voluntary sports clubs should take into consideration their available resources and adapt their financial structures to attain acceptable levels of efficiency and sustainability (Guzmán ; Kirk and Nolan ).…”
mentioning
confidence: 99%